2020
DOI: 10.1111/jpc.14940
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐automatic intraosseous device (EZ‐IO) in a paediatric emergency department

Abstract: Aim Intraosseous access is an alternative to conventional intravenous access. A number of studies have demonstrated the utility and safety of EZ‐IO, a recently introduced semi‐automatic intraosseous device. However, few studies have investigated the use of EZ‐IO in the paediatric emergency setting. The aim of this study was to describe the epidemiological characteristics EZ‐IO use including complications among paediatric patients in a paediatric emergency department. Methods We conducted a retrospective descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The few references made to extravasation in previous reports demonstrated that EZ‐IO and other IO insertion devices were not perfectly safe and occasionally caused complications, such as fracture, infection (osteomyelitis), skin necrosis, and compartment syndrome 14–16 . Another study also reported that dermal abrasion can occur as a complication during IO insertion with EZ‐IO 13,17 . Extravasation was also reportedly the most common complication associated with IO use, with a frequency of occurrence ranging from 10% to 17.5% 3,7,18 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The few references made to extravasation in previous reports demonstrated that EZ‐IO and other IO insertion devices were not perfectly safe and occasionally caused complications, such as fracture, infection (osteomyelitis), skin necrosis, and compartment syndrome 14–16 . Another study also reported that dermal abrasion can occur as a complication during IO insertion with EZ‐IO 13,17 . Extravasation was also reportedly the most common complication associated with IO use, with a frequency of occurrence ranging from 10% to 17.5% 3,7,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that EZ‐IO was successfully used in children at a rate higher than 90%, it was also safe and easy to use, even for novices 3,7‐12 . A previous, retrospective, descriptive study of EZ‐IO use in the pediatric emergency department setting confirmed its high success rate and the rate of complications associated with its use 13 . Complications related to securing an IO line include extravasation, osteomyelitis, fracture, and growth plate injury 14–16 .…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations